PENINGKATAN KUALITAS PELAYANAN TOKO HIJAB AMIRA SURAKARTA DENGAN MENGGUNAKAN APLIKASI FASHION HIJAB BERBASIS ANDROID - tyas, Rachmawati Sunaring; Dewanta, Wika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
Tighter competition in selling muslimah fashion, especially hijab, demands seller to be able survive in hijab fashion industry. The strategy of sale which is conducted must be able to improve customer’s satisfaction in gaining service quality. In this case, hijab shop is as one of providers about muslimah needs. Android is an alternative software chosen for assisting Amira hijab shop in Surakarta in order to do service innovation., Sale strategy by Amira hijab shop in Surakarta is done by android-based Fashion Hijab application which hopes giving excellent service and hadling customers’ complaint. The Fashion Hijab application design of Amira hijab shop in Surakarta can be done by using online shop website with base of CMS Wordpress resulting “Toko Hijab Amira Surakarta” named hijabamira.com, which is continued by doing convertion from website to android aplication using Website 2 APK Builder Pro.After Fashion Hijab application implementation of Toko Hijab Amira Surakarta for two months, the writer wants to know how high is the affect of system quality,information quality towards customer’s quality, and service quality towards customer’s satisfaction as system user who continually affects benefit gotten by Toko Hijab Amira Surakarta. To analyze the application, the writer applies the models of information success system DeLone and McLean which can be used for measuring how far the application of information system is. This research uses descriptive quantitative approach along with convenience sampling technique. The sample and population in this research is the customers of Toko Hijab Amira Surakarta. Data collection technique is done by observation and questionnaire after implementing Fashion Hijab android-based application. By using Structural Equation Modelling (SEM) research method, it can know the relationship precision among variables of system, information, and service qualities; customer; customer’s satisfaction; and the affect of Toko Hijab Amira Surakarta ‘s benefit.There is recommendation to information and system qualities which is hoped Fashion Hijab application can be more effective and easier to use by customer of Toko Hijab Amira Surakarta, so that customer’s satisfaction and net benefit earned by Toko Hijab Amira Surakarta become better